Numerical simulation of solar chimney power plant adopting the fan model. (October 2018) - Rabehi, Rayan; Chaker, Abla; Ming, Tingzhen; Gong, Tingrui
Abstract: Numerical simulations and design of solar chimney power plant adopting the fan model was presented in this study. A mathematical model describing fluid flow and heat transfer has been set up for the three regions of solar chimney power plant: collector, chimney and turbine. The Spanish prototype was chosen as an example for numerical simulation that incorporates turbine model, simulation during turbine operation and no load conditions were compared. For this purpose a simulation of 3D solar chimney power plant system with the standard k-ε turbulence model was developed, using CFD Ansys Fluent. Furthermore the effect of turbine operation and the influences of pressure drop across the turbine and solar radiation were investigated and the results revealed that the variation of solar radiation has an evident effect on the flow and heat transfer characteristics. Meanwhile the influence of turbine pressure drop on the collector efficiency was slight, while has a considerable effect on the power output. Highlights: 3-D numerical simulation for the Spanish SCPP prototype is performed. The simulation results in no-load condition and during turbine operation were compared. The influence of solar radiation on the flow and heat transfer characteristics was analyzed. The effect of turbine pressure drop on the collector efficiency and power output was investigated.